Comparison of ESI and START Triage in Emergency Patient Prioritization: A Literature Review - Akbar, Bayu; Kanita, Maria Wisnu (Poltekkes Kemenkes Surakarta, 2026)
Background: Emergency departments require effective triage systems to prioritize patients based on clinical urgency and resource needs. The Emergency Severity Index (ESI) and Simple Triage and Rapid Treatment (START) are widely used methods with distinct approaches and applications; however, comprehensive comparisons between them remain limited. This study aimed to analyze and compare the effectiveness of ESI and START in prioritizing emergency patients. Methods: This study employed a systematic literature review of articles published between 2020 and 2026. Data were obtained from Google Scholar and ScienceDirect using keywords related to ESI, START, and emergency triage. Articles were selected based on predefined inclusion and exclusion criteria, focusing on relevance, study design, and population. A total of 10 articles met the criteria and were included in the analysis. Data were analyzed using critical appraisal to synthesize findings. Results: START demonstrated significantly faster triage time (11 seconds) than ESI (18 seconds) (p < 0.001). ESI showed higher accuracy and predictive validity for clinical outcomes, including mortality, ICU admission, and resource utilization. Patients categorized as ESI level 1 had higher mortality (17%), with predictive performance (sensitivity 82.1% and negative predictive value 99.9%). In contrast, START showed acceptable sensitivity but carried risks of over-triage and under-triage. Some studies found no significant relationship between ESI and response time (p > 0.05). Conclusion: ESI provides more accurate patient classification in routine emergency settings, whereas START enables faster decision-making and is suited for mass casualty incidents. The selection of triage systems should consider clinical context and resource availability.